Pengaruh Gaya Kepemimpinan dan Disiplin Kerja terhadap Kinerja Karyawan pada PT. Perum DAMRI di Makassar - Sampeluna, Veni; Sambara, Kordiana; Bandhaso, Mira Labi (YASIN, 2025)
Effective leadership style and work discipline are crucial factors influencing employee performance, yet limited studies have explored their combined impact within the transportation sector. This study aims to analyze the influence of leadership style and work discipline on employee performance at PT. Perum DAMRI in Makassar. A quantitative research method with a descriptive approach was employed. The population consisted of all employees of PT. Perum DAMRI Makassar, with a sample selected using a specific sampling technique. Data were collected through questionnaires distributed to respondents and analyzed using correlation coefficient analysis, coefficient of determination (R²), and T-test to determine the significance of the independent variables' influence on the dependent variable. The findings indicate that both leadership style and work discipline significantly affect employee performance. This suggests that effective leadership and high work discipline contribute to increased productivity and work quality among employees at PT. Perum DAMRI Makassar. These results highlight the importance of fostering strong leadership and maintaining strict work discipline to enhance overall organizational performance.